On Submanifolds of (kappa, mu) Contact Metric Manifolds (Dhaka University Journal of Science, 2013)
The object of the present paper is to obtain conditions of integrability of some distributions of semi-invariant submanifolds of contact metric manifolds with ? belonging to (?, ?) -nulity distribution. Dhaka Univ. J. Sci. 61(1): 93-96, 2013 (January) DOI: http://dx.doi.org/10.3329/dujs.v61i1.15103